ISLAM DI KERAJAAN SAMBAS ANTARA ABAD XV – XVII: STUDI AWAL TENTANG ISLAMISASI DI SAMBAS - Risa Risa (Khatulistiwa, 2014)
The Kingdom of Sambas from historical perspectives existed before the conquest Majapahit. In authentic existence it had looked when it became a vassal state of Majapahit since the 14th century until the second half of the mid-17th century. Even so, the islamization of the region for that matter has already started since 1407 M, marked by the establishment of the Chinese Muslim community Hanafi. However the process of islamization in Sambas could not be released from the role of Muslim Chinese traders, later Muslim traders also involve India and Arabia. However, in the 15th century, the development of Islam is still confined to port until the centers in small towns that became central to the economy and the more established in the 16th century. The islamization is getting intensive and the integration of Islamic values in social governance when a political marriage between Raden Sulaiman (from Brunei) and Mas Ayu Bungsu (of the Old Sambas). The Sultanate of Sambas in the next period (1630 M) the more significant contributions to the development of Islam in Sambas.